Structural Basis for Evasion of Nutritional Immunity by the Pathogenic Neisseriae - Yadav, Ravi; Noinaj, Nicholas; Ostan, Nicholas; Moraes, Trevor; Stoudenmire, Julie; Maurakis, Stavros; Cornelissen, Cynthia Nau (Frontiers in Microbiology, 2020)
The pathogenic Neisseria species are human-adapted pathogens that cause quite distinct diseases. N. gonorrhoeae causes the common sexually-transmitted infection, gonorrhea while N. meningitidis causes a potentially-lethal form of bacterial meningitis. During infection, both pathogens deploy a number of virulence factors in order to thrive in the host. The focus of this review is on the outer membrane transport systems that enable the Neisseriae to utilize host-specific nutrients, including metal-binding proteins such as transferrin and calprotectin. Because acquisition of these critical metals is essential for growth and survival, understanding the structures of receptor-ligand complexes may be an important step in developing preventative or therapeutic strategies focused on thwarting these pathogens. Much can also be learned by comparing structures with antigenic diversity among the transporter sequences, as conserved functional domains in these essential transporters could represent the pathogens’ “Achilles heel”. Towards this goal, we present known or modeled structures for the transport systems produced by the pathogenic Neisseria species, overlapped with sequence diversity derived by comparing hundreds of neisserial protein sequences. Given the concerning increase in N. gonorrhoeae incidence and antibiotic resistance, these outer membrane transport systems appear to be excellent targets for new therapies and preventative vaccines.